Model Pembelajaran Experiential Learning "Kemampuan Berpikir Kritis" Peserta Didik: (Experiential Learning Model of Students' â€œCritical Thinking Abilityâ€) - Try Susanti; Fifi Murniasari; Diandara Oryza (BIODIK, 2023)
Based on the results of the pre-research conducted at SMA Negeri 11 Muaro Jambi, it is known that biology learning activities have not been active,Â  the tendency of students to receive information from educators. The formulation of the problem of this research is whether there is an effect of Experiential Learning model on the critical thinking skills at of students SMA Negeri 11 Muaro Jambi. The purpose of this research is to find out the effect of the Experiential Learning Model on the Critical Thinking Skills of the students At SMA Negeri 11 Muaro Jambi. This research method is a quantitative research using Postest-Only Control Design, while data collection is with the final technique (Post-test). Data analysis with ttest. The sampling technique used is Simple Random Sampling with a sample of 20 students in the experimental class and 20 students in the control class. Data were analyzed using normality test, homogen test, and hypothesis testing through SPPS Version 26. The data obtained is then analyzed by comparing the average value of critical thinking skills in the control class with the experimental class, the avarage value for critical thinking skills using the experiential learning model is higher, which is 85.00, while the control class is 74,10. From the test at a significant level of 5% = 1,638 and 1% = 2.353 obtained 1,638 < 2.447 > 2,353 so tcount > ttabel or Ho is rejected and Ha is accepted with the result of sig (2-tailed) is 0.000 < 5% which means there is a significant different between ability critical thingking of student who use the Experiential Learning (EL) learning model and those who do not use the Experiential Learning (EL) learning model at SMA Negeri 11 Muaro Jambi. Abstrak. Berdasarkan hasil pra penelitian yang dilaksanakan di SMA Negeri 11 Muaro Jambi diketahui bahwa kegiatan pembelajaran biologi belum aktif, kecenderungan peserta didik menerima informasi dari pendidik, peserta didik belum mampu memberikan penjelasan sederhana. sehingga kemampuan berpikir kritis masih tergolong rendah. Salah satu model pembelajaran yang cukup bervariasi dan tentunya dapat melibatkan peran aktif siswa dalam kegiatan pembelajaran adalah model pembelajaran Experiential Learning. Penelitian ini bertujuan untuk mengetahui pengaruh model pembelajaran Experiential Learning terhadap kemampuan berpikir kritis peserta didik di SMA Negeri 11 Muaro Jambi. Metode penelitian ini merupakan penelitian kuantitatif dengan menggunakan desain Posttest Control Group Design sedangkan pengumpulan data dengan teknik tes akhir (Pos test). Analisis data dengan ttes. Teknik pengambilan sampel menggunakan Simple Random Sampling dengan sampel berjumlah 20 peserta didik di kelas eksperimen dan 20 peserta didik di kelas kontrol. Data dianalisis menggunakan uji normalitas, uji homogenitas, dan uji hipotesis melalui SPPS Versi 26. Data yang diperoleh kemudian dianalisis dengan membandingkan rata-rata perolehan nilai kemampuan berpikir kritis kelas kontrol dengan kelas eksperimen, nilai rata-rata kemampuan berpikir kritis yang menggunakan model pembelajaran Experiential Learning lebih tinggi, yaitu sebesar 85.00, sedangkan kelas kontrol sebesar 74,10. Dari uji ttes pada taraf signifikan 5% = 1,638 dan 1% = 2,353 diperoleh 1,638 < 2,447 > 2,353 jadi thitung > ttabel atau HO ditolak dan Ha diterima dengan hasil sig (2-tailed) adalah 0,000 < 5 % yang berarti terdapat pengaruh yang signifikan antara kemampuan berpikir kritis peserta didik yang menggunakan model pembelajaran Experiential Learning (EL) dengan yang tidak menggunakan model pembelajaran Experiental Learning (EL) di SMA Negeri 11 Muaro Jambi